Application of low-profile patient-specific surgical cutting guides in the management of craniofacial fibrous dysplasia: A case report and review of current surgical approaches - Mahdi Zakeri; Brian Kinard (Oral and Maxillofacial Surgery Cases)
Managing craniofacial fibrous dysplasia (FD) poses significant challenges, particularly in balancing functional and aesthetic outcomes. Traditional approaches often require broad exposure through coronal flaps or midfacial degloving, leading to increased morbidity and extended recovery. This case report highlights a minimally invasive approach for a 20-year-old female with disfiguring zygomaticomaxillary FD. Through computer-aided surgical simulation (CASS), low-profile patient-specific recontouring guides were employed to perform precise bone recontouring through transconjunctival and intraoral incisions. Postoperative imaging confirmed accurate bone removal when superimposed with the preoperative plan. The patient achieved satisfactory facial symmetry with reduced morbidity. This approach demonstrates that combining CASS with low-profile patient specific recontouring guides can optimize outcomes for complex craniofacial FD cases. Further research and comparative studies are necessary to fully assess the long-term benefits of this technique in surgical managing FD and other benign craniofacial lesions.